A study of HB-UWB transfer function model for wireless body area network - Promsrisawat, Pichayanan; Promwong, Sathaporn (My University, 2018)
Many research on wireless communication technologies for short range communication systems. The human body (HB) on ultra wideband (UWB) technology should be study. The wireless HB-UWB transmission waveform can be extremely distorted through a channel even for free-space transmission because of wideband antenna dispersion in HB-UWB system. Therefore, the understand of antenna characteristics with human body, which effects on waveform distortion, is necessary. This paper presents the waveform distortion due to human body in transfer function for wireless body area network (WBAN) applications based on HB-UWB measurement data. The template waveform is considered at the receiver side to maximize the signal to noise ratio (SNR) for evaluation. In this results are evaluate based on the extended Friis' transmission formula. This technique gives very accurate results and is very useful for the design and evaluation of HB-UWB transmission waveform for WBAN technology, especially focusing on the effect of template waveform and waveform distortion in HB-UWB transfer function.
Keywords: BAN; HB-UWB; UWB; WBAN; WUWB